Magnetic and transport properties of a layered compound Ce2Te5. (26th May 2017) - Chen, D; Zhang, S; Yang, H X; Li, J Q; Chen, G F
Abstract: Ce2 Te5 single crystals were successfully grown using RbCl/LiCl flux method. The structure of Ce2 Te5 can be viewed as a combination of CeTe2 and CeTe3 . The experimental results of magnetic susceptibility χ ( T ), isothermal magnetization M ( H ), electrical resistivity ρ ( T ), and heat capacity C ( T ) show two clear anomalies at 5.1 and 2.3 K, which correspond to a ferrimagnetic and a possible antiferromagnetic transition, respectively. Both of ρ ( T ) and C ( T ) confirm a third transition at 0.9 K. The resistivity shows a huge anisotropy with the current applied in I ⊥ b and I ∥ b directions. Our experimental results prefer the scenario that the three consecutive transitions in Ce2 Te5 are attributed to two different kinds of origin, which are independent and responsible for the magnetic orders observed in CeTe2 and CeTe3 .